Protective Effect of Nerolidol on Paclitaxel-Induced Reproductive Toxicity in Rats: Oxidative Stress and Inflammation - Ayhan, Idris; Turkmen, Nese Basak; Taslidere, Asli; Aydin, Muhterem; Ciftci, Osman (Wiley, 2025)
Paclitaxel (PAC), derived from Taxus brevifolia, is used to treat solid tumours but causes reproductive toxicity due to oxidative stress, affecting sperm quality and testicular tissue. Nerolidol (NRL), an antioxidant sesquiterpene alcohol, has not been studied for its potential to reduce PAC-induced reproductive damage. This study investigates NRL's ability to mitigate PAC-induced reproductive toxicity in rats. Forty healthy adult male Spraque Dawley rats were randomly divided into four equal groups (Control, PAC, NRL, PAC + NRL). PAC was given intraperitoneally at a dose of 2 mg/kg once a week for 4 weeks. NRL was given orally at a dose of 100 mg/kg/day for 4 weeks. Control group received PAC and NRL vehicles. After 4 weeks, testis tissue samples were collected, and parameters, including oxidants, antioxidants, sperm motility, density, abnormal spermatozoon ratios and cytokines, were measured. PAC administration increased oxidant levels and decreased antioxidant enzyme activities. Nerolidol mitigated these alterations significantly. Similarly, PAC elevated IL-1, IL-6, TNF-alpha levels and lowered IL-10 levels, these effects attenuated by nerolidol in the PAC + NRL group. In conclusion, it was determined that PAC induces reproductive toxicity through oxidative stress, and NRL demonstrates potential in ameliorating these effects through its antioxidant activity.
Keywords: antioxidant; nerolidol; oxidative stress; paclitaxel; reproductive toxicity